A coordinated investigation of the gravity wave breaking and the associated dynamical instability by a Na lidar and an Advanced Mesosphere Temperature Mapper over Logan, UT (41.7°N, 111.8°W). Issue 8 (20th August 2014) - Cai, Xuguang; Yuan, Tao; Zhao, Yucheng; Pautet, Pierre‐Dominique; Taylor, Mike J.; Pendleton, W. R.
Abstract The impacts of gravity wave (GW) on the thermal and dynamic characteristics within the mesosphere/lower thermosphere, especially on the atmospheric instabilities, are still not fully understood. In this paper, we conduct a comprehensive and detailed investigation on one GW breaking event during a collaborative campaign between the Utah State University Na lidar and the Advanced Mesospheric Temperature Mapper (AMTM) on 9 September 2012. The AMTM provides direct evidence of the GW breaking as well as the horizontal parameters of the GWs involved, while the Na lidar's full diurnal cycle observations are utilized to uncover the roles of tide and GWs in generating a dynamical instability layer. By studying the changes of the OH layer peak altitude, we located the wave breaking altitude as well as the significance of a 2 h wave that are essential to this instability formation. By reconstructing the mean fields, tidal and GW variations during the wave breaking event, we find that the large‐amplitude GWs significantly changed the Brunt–Vaisala frequency square and the horizontal wind shear when superimposed on the tidal wind, producing a transient dynamic unstable region between 84 km and 87 km around 11:00 UT that caused a subsequent small‐scale GW breaking.